Mathematical model of thermo-dynamical processes during contacting of gradient-heated billet with flat die - Кухарь, В.В.; Тузенко, О.А.; Балалаева, Е.Ю.; Нагнибеда, Н.Н. (Problems of Tribology, 2016)
The models of a heat transfer from billet that unregulated heated on length to the flat die are considered in this pa-per. The recurrent certainly-difference mathematical model of a temperature fields changes in the billet and the die are devel-oped. This model allows defining the initial distribution of temperatures in billet for choice an electro-thermal heater of a necessary design